Peritoneal Dialysis in Pakistan: Getting out of Second Gear: An Update on PD Utilization from Pakistan by the PD Working Group of Pakistan Society of Nephrology. (Pakistan Journal of Kidney Diseases, 2026)
Pakistan has huge burden of patients requiring renal replacement therapy. It is noteworthy that renal transplantation and hemodialysis services have grown exhaustingly and exponentially to meet this huge demand. Paradoxically the utilization of peritoneal dialysis as modality of renal replacement therapy has remained less than 1 per cent since its introduction in the 1980s to-date. However, initiatives in the last decade have led to an 8-fold increase in the number of peritoneal dialysis patients. This article highlights the barriers to PD utilization in Pakistan, their potential solutions, what have been sorted and what hurdles remain to be addressed. Additionally this articles sheds light on the need for governmental support, innovation potential of private sector and formulating a win-win situation for all stakeholders.